New threats and countermeasures in digital crime and cyber terrorism - Dawson, Maurice, 1982-; Omar, Marwan, 1982- (Information Science Reference, An Imprint of IGI Global, 2015)
"This book brings together research-based chapters and case studies on security techniques and current methods being used to identify and overcome technological vulnerabilities with an emphasis on security issues in mobile computing and online activities"-- Provided by publisher.
Keywords: Computer crimes -- Prevention.; Cyberterrorism -- Prevention.; Computer security.; elektronické knihy; electronic books